2008
DOI: 10.1177/1054773808324655
|View full text |Cite
|
Sign up to set email alerts
|

Family Involvement in Inpatient Care in Taiwan

Abstract: This descriptive, cross-sectional survey study illustrates the roles for and motives of being a family visitor to accompany a hospitalized loved one during hospitalization in a Taiwanese hospital. Family visitors were approached by research assistants on a random basis in acute inpatient units. Among the 1,034 participants, 91% were relatives. About 80.0% of them were present to attend to the patient's physical care, 61.0% to offer psychological support, and 63.5% to express their desire to learn more about th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 12 publications
0
19
0
Order By: Relevance
“…25 27 Importantly, the external validity of our study is limited to similarly developed Western nations as New Zealand. Our findings are less generalisable to countries with constrained healthcare resources (eg, developing nations, where access to care rather than patient choice determines healthcare delivery), or with significantly different cultural orientations (eg, familism in context of Confucian cultures such as Taiwan, where filial piety often precludes conservative care for end-stage renal disease (ESRD)) [29][30][31] .…”
Section: Discussionmentioning
confidence: 73%
“…25 27 Importantly, the external validity of our study is limited to similarly developed Western nations as New Zealand. Our findings are less generalisable to countries with constrained healthcare resources (eg, developing nations, where access to care rather than patient choice determines healthcare delivery), or with significantly different cultural orientations (eg, familism in context of Confucian cultures such as Taiwan, where filial piety often precludes conservative care for end-stage renal disease (ESRD)) [29][30][31] .…”
Section: Discussionmentioning
confidence: 73%
“…Increasing the patient’s costs and request for discharge before the determined time was another consequences of this research from viewpoint of families. According to other researchers increasing hospital costs associated with the presence of family provides the background for dissatisfaction and complaint (18, 29), and in some cases, leads to verbal and physical violence against nurses by patients and their family (30-33)…”
Section: Discussionmentioning
confidence: 99%
“…These results were related to the Chinese filial piety philosophy. Tzeng and Yin indicated that the motives of visiting a hospitalized loved one in Taiwan included fulfilling one of their responsibilities, coming to help voluntarily, showing filial piety for their parent and being afraid that the patient could not obtain appropriate care . The family involvement culture in Taiwan might have placed pressure on family caregivers to stay in the hospital or hire a labourer to take care of their relatives if they themselves were busy.…”
Section: Discussionmentioning
confidence: 99%